Servant Leadership in the Healthcare Literature: A Systematic Review - Demeke GW; van Engen ML; Markos S (Dove Medical Press, 2024)
Getnet Worku Demeke,1,2 Marloes L van Engen,3 Solomon Markos1 1Department of Business Administration and Information Systems, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Management, Kotebe University of Education, Addis Ababa, Ethiopia; 3Institute for Management Research, Radboud University, Nijmegen, the NetherlandsCorrespondence: Getnet Worku Demeke, Tel +251 911 57 13 25, Email getnet.workuu@aau.edu.et; wgetme@yahoo.comAbstract: Servant leadership has received a growing consideration among scholars and practitioners as a viable leadership model capable of bringing positive changes in the increasingly complex healthcare system. The increasing servant leadership literature in healthcare requires an integrated research work that provides a holistic picture of the existing studies. This systematic review aims to synthesize servant leadership conceptualizations, theoretical frameworks, measurement tools, and nomological networks (antecedents, mediators, outcomes, and moderators) associated with prior research in healthcare. A systematic synthesis of 55 pertinent healthcare-specific conceptual and empirical studies demonstrated that servant leadership assumes a crucial role in developing a committed workforce that contributes towards the achievement of performance excellence in healthcare. The review uncovers that the Global Servant Leadership Scale is the most utilized measure of servant leadership in sector-specific studies in healthcare. Moreover, social exchange theory is the dominant underpinning mechanism explaining the influence of servant leadership on specific variables of interest. The findings further revealed that servant leadership has a positive relationship with a range of valued individual and organizational outcomes in healthcare. Our review contributes to the development of servant leadership theory and practice through ascertaining sector-specific studies in the territory of healthcare. We finally conclude by providing a detailed panorama for future healthcare-specific servant leadership research in terms of potential topics, methodological rigor, and less explored variables in prior studies.Keywords: healthcare leadership, health care, healthcare sector, content analysis, nomological network, comprehensive review